Sustainable biomass aerogel with enhanced thermal and mechanical properties by industrial waste fly ash: A simple route for the green synthesis - Ju Li; Lize Yang; Shuo Chen; Guotao Sun (eXPRESS Polymer Letters)
The widespread use of cellulose nanofiber (CNF)-based aerogels is hindered by their limited flame retardancy and mechanical properties. This study addresses these challenges by developing cellulose nanofiber/sodium alginate/fly ash (CNF/SA/FA) aerogel through a one-pot method, utilizing industrial waste fly ash (FA) as a reinforcing material. Various characterization and analytical techniques were employed to evaluate the properties of the CNF/SA/FA aerogel. The findings have revealed that resulting aerogel exhibited excellent thermal insulation performance, with a thermal conductivity of 0.485 W/(m·K), along with an impressive compressive strength of 88.4 kPa and favorable shape processability. Vertical combustion tests demonstrated a V-0 rating, indicating superior flame retardancy, and the aerogel achieved a remarkable 79.16% residual carbon, confirming their effective heat shielding capabilities. Notably, the incorporation of FA significantly enhanced both the thermal and mechanical properties of the composite aerogel, presenting a sustainable and effective solution to optimizing the properties of aerogel for thermal insulation.